Resolution of the membrane moiety of the H+-ATPase complex into two kinds of subunits. - Sone, N (1978)
The H+-translocating ATPase complex from the thermophilic bacterium PS3 (TF0-F1) is composed of a water-soluble part with ATP-hydrolyzing activity (TF1) and a membrane moiety with H+-conducting activity (TF0). TF0 was obtained by treating TF0-F1 with urea and removing contaminations on a carboxymethyl-cellulose column. This TF0 contained only two kinds of subunits, band 6 protein (13,500 daltons) and band 8 protein (5400 daltons), and it was active in H+ conduction and TF1 binding when reconstituted into proteoliposomes (TF0 vesicles). The binding of TF1 to TF0 present in vesicles restored energy-transducing activities, such as ATP-32Pi exchange, dicyclohexylcarbodiimide-sensitive ATPase, and ATP-dependent enhancement of 8-anilinonaphthalene-1-sulfonate fluorescence. Treatments such as protease digestion and chemical modification with acetic anhydride, succinic anhydride, or diazobenzenesulfonic acid destroyed the TF1-binding activity, which was caused by band 6 protein. Band 8 protein was a proteolipid that reacted specifically with dicylcohexyl-carbodiimide and seemed to play a central role in H+ conduction through the membrane.